2020
DOI: 10.1002/btm2.10193
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic therapy reduces iron retention of hemorrhagic plaque

Abstract: Intraplaque hemorrhage (IPH) plays a major role in the aggressive progression of vulnerable plaque, leading to acute cardiovascular events. We previously demonstrated that sonodynamic therapy (SDT) inhibits atherosclerotic plaque progression. In this study, we investigated whether SDT could also be applied to treat more advanced hemorrhagic plaque and addressed the underlying mechanism. SDT decreased atherosclerotic burden, positively altered atherosclerotic lesion composition, and alleviated iron retention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Sonodynamic therapy (SDT) has gained widespread attention recently due to its safety, deep tissue penetration depth, and cost-effectiveness. [244,245] SDT, as a burgeoning therapeutic modality, enables US irradiation to trigger sonosensitizers to generate ROS for CVD therapy. [246,247] For example, Li et al designed US-propelled Janus rod (JR)-shaped micromotors (Pc/Ca@r-JRs) for US-driven thrombus penetration and SDT of thrombosis without using any thrombolytic agents (Figure 18A).…”
Section: Ultrasound-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Sonodynamic therapy (SDT) has gained widespread attention recently due to its safety, deep tissue penetration depth, and cost-effectiveness. [244,245] SDT, as a burgeoning therapeutic modality, enables US irradiation to trigger sonosensitizers to generate ROS for CVD therapy. [246,247] For example, Li et al designed US-propelled Janus rod (JR)-shaped micromotors (Pc/Ca@r-JRs) for US-driven thrombus penetration and SDT of thrombosis without using any thrombolytic agents (Figure 18A).…”
Section: Ultrasound-based Therapymentioning
confidence: 99%
“…Sonodynamic therapy (SDT) has gained widespread attention recently due to its safety, deep tissue penetration depth, and cost‐effectiveness. [ 244,245 ] SDT, as a burgeoning therapeutic modality, enables US irradiation to trigger sonosensitizers to generate ROS for CVD therapy. [ 246,247 ] For example, Li et al.…”
Section: Cvd Therapymentioning
confidence: 99%
“…by activating the ROS-Nrf2-PFN1 signaling pathway and promoted transferrin efflux, which reduced iron retention in plaques and especially in the macrophages. [237] Another representative sonosensitizer is a natural extract represented by hydroxysafflor yellow and curcumin. The former induced THP-1 macrophage autophagy and cleared local inflammation in plaque by inhibiting PI3K/Akt/mTOR induction under US irradiation.…”
Section: Sonodynamic Therapy (Sdt)mentioning
confidence: 99%
“…In recent years, SDT has been elucidated to show the therapeutic effect on atherosclerosis [58][59][60][61][62][63][64]. Studies have shown the SDT-induced foam-cell apoptosis, iron retention alleviation and cytokine secretion inhibition contributed to the stabilization in advanced plaques by using 5aminolevulinic acid, sinoporphyrin sodium, etc [59,61]. Advanced progress has been achieved in clinical trials [65].…”
Section: Othersmentioning
confidence: 99%